Ultrasonic evaluation of weak mold compound/silicon interfaces in IC packages - Yeo, Hwee Chung. (2008)
The quality of interfaces such as that between mold compound and silicon (MC/Si) is a critical issue in the reliability testing of IC packaging and during the manufacturing process. Common defects such as delamination can be detected using C-mode scanning acoustic microscopy with sufficient confidence. However, weak interfaces have often gone undetected and may become potentially defective at a later stage.